2014
DOI: 10.3906/sag-1310-90
|View full text |Cite
|
Sign up to set email alerts
|

Is the combined use of insulin resistance indices, including adipokines, more reliable in metabolic syndrome?

Abstract: IntroductionMetabolic syndrome (MetS) is a clustering of cardiovascular risk factors associated with insulin resistance, central adiposity, hyperglycemia, hypertension, hypertriglyceridemia, and low high-density lipoprotein cholesterol (HDL-C) levels (1,2).Adipokines are secreted by adipose tissue and influence a variety of physiological processes such as food intake control, energy homeostasis, insulin sensitivity, angiogenesis, blood pressure regulation, and blood coagulation (3). They play significant roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…Similar picture was observed when assessing adipokine signaling: adiponectin was significantly lower in MetS2 group (nonpublished data) while visfatin was significantly higher [ 18 ]. Similarly to previous reports [ 26 , 27 ], we observed no difference in resistin levels between the three groups in the present study, although some studies demonstrated significantly higher serum resistin levels in MetS group compared to control group [ 28 , 29 ]. Interestingly, some parameters were statistically higher already when the groups MetS0 and MetS1 were compared.…”
Section: Discussionsupporting
confidence: 89%
“…Similar picture was observed when assessing adipokine signaling: adiponectin was significantly lower in MetS2 group (nonpublished data) while visfatin was significantly higher [ 18 ]. Similarly to previous reports [ 26 , 27 ], we observed no difference in resistin levels between the three groups in the present study, although some studies demonstrated significantly higher serum resistin levels in MetS group compared to control group [ 28 , 29 ]. Interestingly, some parameters were statistically higher already when the groups MetS0 and MetS1 were compared.…”
Section: Discussionsupporting
confidence: 89%
“…The same was elicited by Kural et al [26], who reported that the levels of visfatin were significantly higher in MS than in non-MS individuals. Chang et al [27] also detected the same elevation of visfatin in MS cases and even suggested the use of visfatin as a diagnostic marker in MS.…”
Section: Discussionsupporting
confidence: 53%
“…[ 21,82 ] A previous study showed that the decreased level and negative relation of ADP/LEP with insulin suggested that the ADP/LEP ratio could be used as an insulin sensitivity index. [ 83 ] In the present study, combined treatment of DAPA and LPZ significantly increased the ADP/LEP ratio more than either drug alone, indicating a beneficial effect of this combination on the adipokine profile and resulting in better improvement of insulin sensitivity. Moreover and interestingly, the results of the present study demonstrated for the first time the role of DAPA and/or LPZ on ADP/LEP ratio as a useful estimate of IR.…”
Section: Discussionsupporting
confidence: 55%
“…[21,82] A previous study showed that the decreased level and negative relation of ADP/LEP with insulin suggested that the ADP/LEP ratio could be used as an insulin sensitivity index. [83] In the PPAR-γ plays a vital role in controlling the storage and release of fats and glucose, as well as lipid metabolism, regulating IR, blood glucose, cell growth, and differentiation, vascular inflammation reaction, as well as influencing the pathologic processes of vascular sclerosis. [84] Therefore, PPAR-γ has become the focus of investigations on antidiabetic drugs.…”
Section: Glut-2 Gene Expressionmentioning
confidence: 99%